UMUR SIMPAN DAN DAYA TERIMA DODOL EKSTRAK DAGING DAN KULIT BUAH NAGA MERAH - Farah Meidilla Az Zahra; Elida; Lucy Fridayati; Rahmi Holinesti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: "The shelf life of a food product is the period during which the product remains safe and maintains its sensory, chemical, physical, and microbiological quality according to expected standards. For semi-moist products such as dodol, key facto rs affecting shelf life include moisture content, water activity (aw), pH, the presence of microorganisms (mold/yeast), packaging conditions, and storage temperature. Hedonic testing is a sensory evaluation method conducted to determine the level of consumer preference for a product. Both the flesh and peel of red dragon fruit contain betalain pigments (betacyanins) and phenolic compounds that function as natural antioxidants. Utilizing the peel can reduce agricultural waste while enhancing the nutritional aspects and oxidative stability of the product. Therefore, comparing the extract of red dragon fruit flesh and peel in dodol products is relevant from the perspectives of food technology and sustainability. This assessment covers shape, color, aroma, texture, and taste, evaluated based on a subjective scale. This study aims to analyze the differences in shelf life and acceptability (hedonic test) between dodol using red dragon fruit flesh and peel extracts. The research method employed is a mixed method, combining descriptive qualitative analysis for shelf-life observation and quantitative analysis for the hedonic test with 50 panelists. The results showed that the optimal shelf life of the product is 10-12 days at room temperature. Statistical tests indicated that significant differences were only found in the color variable, while aroma, texture, and taste showed no significant differences between the two types of dodol."   Keywords: dodol; red dragon fruit flesh; red dragon fruit peel; shelf life; hedonic test.   Abstrak: Umur simpan suatu produk pangan adalah periode di mana produk tersebut tetap aman dan mempertahankan mutu sensori, kimiawi, fisik, dan mikrobiologis sesuai standar yang diharapkan. Untuk produk semi-basah seperti dodol, faktor-faktor kunci yang mempengaruhi umur simpan meliputi kadar air, aktivitas air (a_w), pH, keberadaan mikroorganisme (jamur/yeast), kondisi pengemasan, dan suhu penyimpanan. Uji hedonik adalah metode evaluasi sensori yang dilakukan untuk mengetahui seberapa besar tingkat kesukaan seseorang terhadap suatu produk. Daging dan kulit buah naga merah mengandung pigmen betalain (betasianin) dan senyawa fenolik yang berfungsi sebagai antioksidan alami. Pemanfaatan kulit dapat menurunkan limbah pertanian sekaligus menambah aspek nutrisi dan stabilitas oksidatif produk. Oleh karenanya, membandingkan ekstrak daging dan ekstrak kulit buah naga merah pada produk dodol relevan dari sisi teknologi pangan dan keberlanjutan. Penilaian ini mencakup bentuk, warna, aroma, tekstur dan rasa yang dinilai berdasarkan skala subjektif. Penelitian ini bertujuan untuk menganalisis perbedaan umur simpan dan daya terima (uji hedonik) antara dodol yang menggunakan ekstrak daging dan kulit buah naga merah. Metode penelitian yang digunakan adalah mixed method yang menggabungkan analisis kualitatif deskriptif untuk pengamatan umur simpan dan kuantitatif untuk uji hedonik dengan 50 panelis. Hasil penelitian menunjukkan bahwa masa simpan optimal produk adalah 10-12 hari pada suhu ruang. Uji statistik menunjukkan perbedaan signifikan hanya ditemukan pada variabel warna, sementara aroma, tekstur, dan rasa tidak menunjukkan perbedaan signifikan antara kedua jenis dodol tersebut.   Kata kunci: dodol; daging buah naga; kulit buah naga; umur simpan; uji hedonik